Effects of Crisis Response Strategies on Purchase Intention - Sohaib Uz Zaman; Amir Ali; Ghazmeen; Syed Hassan Ali (Review Journal of Social Psychology & Social Works, 2025)
This study aims to explore the impact of online crisis response strategies on consumer behavior in the digital marketplace. Specifically, it investigates how these strategies influence online purchase intention and online brand attitude, providing insights into how consumers perceive and react to brand responses during crises. Furthermore, the study examines the mediating role of online brand attitude in linking crisis response strategies to purchase intention, highlighting the importance of brand perception in consumer decision-making. Additionally, it assesses the moderating effect of brand perceived usefulness on the relationship between online brand attitude and purchase intention, proposing that a higher perceived usefulness strengthens this relationship. By integrating these factors, the study offers a comprehensive understanding of consumer responses to brand crisis management in the online environment.